Amyloid-β oligomers in the nucleus accumbens decrease motivation via insertion of calcium-permeable AMPA receptors - Guo, Changyong; Wen, Di; Zhang, Yihong; Mustaklem, Richie; Mustaklem, Basil; Zhou, Miou; Ma, Tao; Ma, Yao-Ying (Molecular psychiatry, 2022)
It is essential to identify the neuronal mechanisms of Alzheimer's Disease (AD)-associated neuropsychiatric symptoms, e.g., apathy, before improving the life quality of AD patients. Here, we focused on the nucleus accumbens (NAc), a critical brain region processing motivation, also known to display AD-associated pathological changes in human cases. We found that the synaptic calcium permeable (CP)-AMPA receptors (AMPARs), which are normally absent in the NAc, can be revealed by acute exposure to Aβ oligomers (AβOs), and play a critical role in the emergence of synaptic loss and motivation deficits. Blockade of NAc CP-AMPARs can effectively prevent AβO-induced downsizing and pruning of spines and silencing of excitatory synaptic transmission. We conclude that AβO-triggered synaptic insertion of CP-AMPARs is a key mechanism mediating synaptic degeneration in AD, and preserving synaptic integrity may prevent or delay the onset of AD-associated psychiatric symptoms.